Influence of salinity on growth, nutrient utilization, and gene expression of giant freshwater prawn (Macrobrachium rosenbergii) - Farhana Ahamed Shanila; Md. Rajib Sharker; Md. Rafiqul Islam; Niels O. G. Jørgensen; Mohammad Lokman Ali (PLoS ONE, 2026)
Salinity is one of the most influential eco-hydrological factors that affect the molting, growth, and other physico-biochemical responses of crustaceans. A 56-day in vivo experiment was conducted to assess the effects of variable salinities on growth attributes, feed utilization, and gene expression profile of Macrobrachium rosenbergii. Juveniles of M. rosenbergii that were exposed to salinities of 0, 3, 6, 9, and 12 ppt in triplicate, and designated as control, T1, T2, T3, and T4, respectively. Higher weight gain (WG), %WG, specific growth rate (SGR), feed conversion ratio (FCR), and protein efficiency ratio (PER) were recorded at 3 ppt than at other salinities. A salinity of 3 ppt also showed higher values of condition factor (CF), and survival of M. rosenbergii . A polynomial regression analysis indicated that the optimal salinity for WG and SGR of M. rosenbergii were 3.12 and 3.80, respectively. A significant decrease in the molt-inhibiting hormone (MIH) and an increase in the chitinase (CHIT) gene expression were documented at 3 ppt compared to control. The mRNA transcripts of stress response genes were significantly downregulated, and immune-related genes were upregulated at 3 ppt salinity, compared to the other salinities. Although the expression of antioxidant-related genes was upregulated when rearing at 3 ppt salinity, no significant differences were found relative to other salinities. Our findings suggest that M. rosenbergii reared at 3 ppt salinity show promising improvements in growth attributes by modulating the expression profile of physico-biochemical response genes reared at low temperature.